Legal Analysis of Impact of Revised BIMCO Clauses on Crew Health and Safety During COVID-19 Era - Boviatsis, Michail; Daniil, Georgios (Transactions on Maritime Science, 2022)
This paper evaluates how the revised BIMCO Crew Change Clause 2020 affected crew health during this period. To satisfy the need for specific clauses, regulating the contractual relationships during the COVID-19 period, BIMCO created sets of clauses, such as the BIMCO Crew Change Clauses for Time Charter Parties (2020). The rationale of those clauses was based upon the pre-existing BIMCO Infectious or Contagious Diseases Clause for Voyage and Time Charter Parties 2015, but it was evidenced that the COVID-19 virus had many intricacies. Thus, new sets of rules are presently emerging to eliminate the gaps created. The basic downside of this legislation and the focus of this paper is to prove that these clauses are focused only on regulating the contractual relationship, without actually taking into consideration the crews’ health and safety. The analysis is focused on the impact of a COVID-19 incident on four specific legal aspects, i.e. i) vessels’ seaworthiness, ii) charter parties, iii) port safety, and iv) refusal of orders. There is also an analysis of the imminent Decease Clause 2021 and its actual impact upon the shipping industry. The analysis of the relevant legislation is based on legal doctrine, dominant form in legal research, aiming to provide a systematic exposition of the legal and regulatory principles. It analyzes the relationship between those principles to provide clarifications, utilizing legislation and relevant case law as the primary source of data. This research method is qualitative and is very similar to critical analysis, whose application is performed through (a) research and description of the existing legislation, (b) prescription, whose essence is to explore the statutory framework, locate the critical points, and assess the effectiveness of legislation on protecting the crew health and safety, and (c) evaluation of possible amendments or additions. The majority of studies conclude that shipping companies will be able to protect crew health and safety only through proactive measures and due diligence. The revised BIMCO terms on crew changes during Covid-19 and the new Disease Clause 2021 sadly did not have crew protection as their top priority. In most parts they tried to allocate and even mitigate the risk of the contracting parties, providing “windows” of opportunity for both sides to be excepted from any liability. Based on the analysis of resources, the new clause is not engaging the concept of proactive measures, unquestionably the most important method for the preservation of crew health usually referred to as “exercising due diligence”. It is a fact that BIMCO protects the clients’ interests, with the clients being the charter parties. It is also valid that the shipping industry supported the nations during the COVID-19 outbreak, but the BIMCO clauses were concentrated on the preservation of contractual relationships, leaving the concept of crew health and safety uncharted.